Sodium Intake among Adults in the Western Region of Saudi Arabia - Mumena, Walaa; MohammedSaeed, Walaa; Madkhali, Amirah; AlJabri, Haneen; AlHarbi, Samaher; Taher, Sarah; AlHujuri, Shahad; Hammouda, Sahar (Progress in Nutrition, 2022)
Background/Aim: This study aimed to assess sodium intake and its predictors among adults residing in the Western region of Saudi Arabia. Material and Methods: In this cross-sectional study, data were collected from 494 adults aged 20-50 years. Participants were recruited from two public universities and public places in Madinah and Jeddah. Data about demographics, sodium intake, salt-related practices, and anthropometrics (height and weight) were collected through face-to-face interviews. The World Health Organization (WHO) sodium intake recommendation (< 2000 mg per day) was used as a cutoff to categorize participants. Results: Median sodium intake was 4273 mg per day (IQR 3053-5979). The sodium intake in 93.5% of participants exceeded the WHO recommendation of < 2000 mg per day. Weight status and sex were not linked to sodium intake. Salt use while cooking predicted a lower sodium intake (p=.009), whereas salt use at the table and frequency of fast-food consumption predicted a higher intake of sodium (p=.039 and p=.001, respectively). Making effort to reduce salt intake and using salt alternatives did not predict sodium intake. Conclusion: Adults residing in the Western region of Saudi Arabia consumed high amounts sodium. Excessive sodium consumption among the study population highlights the urgent need for interventions to reduce sodium intake among adults in Saudi Arabia.